Integrasi Nilai-Nilai Sosial dalam Kurikulum Pendidikan Nasional - Intan Disha Afriani; Dzakia Khairunnisa; Gusmaneli (CV. ITTC INDONESIA, 2024)
The integration of social values ​​in character education is very important to form individuals who are not only academically intelligent, but also have good personalities. Character education aims to shape students' attitudes and behavior so that they become responsible and ethical citizens. Through a curriculum approach that accommodates social values, students can develop the empathy, social skills and social awareness needed to contribute positively to society. The role of teachers as role models and creators of a conducive learning environment is also very crucial in instilling social values. However, challenges in integrating social values, such as lack of understanding among educators, cultural differences, and the influence of the media, need to be overcome through collaboration between government, schools, and society. In this way, character education based on social values ​​can be realized and have a positive impact on the development of students and society as a whole.